1984
DOI: 10.1002/qua.560250209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the inadequacies of some semi‐empirical MO methods as theories of structure and reactivity

Abstract: Essential defects of present-day semiempirical methods (CNDO/%, CNDO/S, MIND0/3, MNDO) can be identified on two levels. First, the formalism shared by nearly all these methods treats parametric expressions, supposed to refer to Lowdin orthogonalized orbitals, as transferable. At best, this idea is approximately valid for the B functions for strong bonds. Second, the expressions used for these approximately transferable functions are based on inadequate arguments. As a result, the errors in many terms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Ions produced by doping the solid may also lead to perturbed chain excitations [52]. Orenstein and Baker [42], however, have observed a photogenerated intrinsic optical transition at -0.5 eV in transpolyacetylene and speculated that the feature may be due to radical cation absorption of the type considered here. Elucidation of the low-temperature optical spectrum is further complicated by the probable presence of the corresponding anions.…”
Section: E Extrapolation To Longer Linear Polyenesmentioning
confidence: 92%
See 1 more Smart Citation
“…Ions produced by doping the solid may also lead to perturbed chain excitations [52]. Orenstein and Baker [42], however, have observed a photogenerated intrinsic optical transition at -0.5 eV in transpolyacetylene and speculated that the feature may be due to radical cation absorption of the type considered here. Elucidation of the low-temperature optical spectrum is further complicated by the probable presence of the corresponding anions.…”
Section: E Extrapolation To Longer Linear Polyenesmentioning
confidence: 92%
“…The proposed adjustment simply compresses the divergence to the experimental-energy distribution based on best estimates from selected UPS studies. DeBruijn [42] further showed that such errors are not strongly manifest in the evaluation of excitations to the virtual levels. These scaling procedures have been applied to the study of the ionstate properties of additional systems with apparent success [20,37,43].…”
Section: Computationalmentioning
confidence: 97%
“…Apart from this example, it is evident that orthogonalization effects, ϕ0emHμν=λ=1Mσ=1M0.5em() χ0emS12μλ0.5em χ0emHλσ0.5em χS12σν, cannot be captured by introducing element‐dependent parameters which was, for instance, pointed out in Refs. . The matrix element ϕ H μν depends on contributions from all matrix elements of χ H .…”
Section: The Modified Neglect Of Diatomic Overlap Modelmentioning
confidence: 99%
“…Taking ϕ0emHμνMNDO to be proportional to χ S μν has a long history and the initial idea is ascribed to Mulliken . In general, Equation was, however, found to be a poor approximation to the analytical value of ϕ H μν , irrespective of the chosen values for βnormall()μZnormalI This can be attributed to the fact that ϕ H μν is not necessarily proportional to χ S μν (for an example, see Figure ). Hence, not even the nodal structure of ϕ0emHμν=ϕ0emHμν(Rfalse˜IJ) is captured correctly.…”
Section: The Modified Neglect Of Diatomic Overlap Modelmentioning
confidence: 99%
See 1 more Smart Citation